2022
DOI: 10.3390/jcm11030597
|View full text |Cite
|
Sign up to set email alerts
|

New Recovery Strategies in Motor and Cognitive Functions, before, during and after Home-Confinement COVID-19, for Healthy Adults and Patients with Neurodegenerative Diseases: Review

Abstract: Distancing and confinement at home during the Coronavirus Disease 2019 (COVID-19) outbreak has led to worsening of motor and cognitive functions, both for healthy adults and for patients with neurodegenerative diseases. The decrease in physical activity, the cessation of the intervention of the recovery and the social distance imposed by the lockdown, has had a negative impact on the physical and mental health, quality of life, daily activities, as well as on the behavioral attitudes of the diet. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Both healthy adults and patients with neurodegenerative diseases have experienced worsening motor and cognitive functions because of distancing and confinement at home during the COVID-19 outbreak. The lockdown has negatively affected the physical and mental health, the quality of life, daily activities, and diet behaviour due to the decrease in physical activity, the stoppage of the recovery intervention and the social distance it imposed [ 26 , 27 ]. We found that 33.0% of patients had racing thoughts, while 9.0% of the controls reported racing thoughts ( p < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…Both healthy adults and patients with neurodegenerative diseases have experienced worsening motor and cognitive functions because of distancing and confinement at home during the COVID-19 outbreak. The lockdown has negatively affected the physical and mental health, the quality of life, daily activities, and diet behaviour due to the decrease in physical activity, the stoppage of the recovery intervention and the social distance it imposed [ 26 , 27 ]. We found that 33.0% of patients had racing thoughts, while 9.0% of the controls reported racing thoughts ( p < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a more rapid decline in functional status was observed during periods of restrictive measures [27]. The most notable changes were associated with disturbances in cognitive functions and emotional states, deterioration in well-being and quality of life, disrupted sleep patterns, and unhealthy eating behaviors, particularly among women [28].…”
Section: Introductionmentioning
confidence: 97%